1991
DOI: 10.1042/bj2760471
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of chromogranin A-derived peptides in bovine gut, pancreas and adrenal medulla

Abstract: Chromogranin A is produced in many endocrine cell types, and is widely used as a marker in endocrine-cell pathology and secretory-cell biology. There is some evidence that it may be proteolytically processed to yield the putative pancreatic regulatory peptide, pancreastatin, and, in order to characterize the relevant pathways in gastrointestinal and pancreatic endocrine cells, we have used, in radioimmunoassay, site-directed antibodies to pancreastatin itself (L331) and to a sequence of chromogranin A immediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
50
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(58 citation statements)
references
References 36 publications
8
50
0
Order By: Relevance
“…A parallel is often drawn between VGF and the chromograninsecretogranin family of proteins, because of their selective localisation in secretory granules, as well as their role as precursors of multiple bioactive peptides (Helle 2004). Chromogranins, too, are differentially processed in gastric endocrine cells (Watkinson et al 1991, Watkinson & Dockray 1992, Portela-Gomes & Stridsberg 2002), although to a profile different from the one we observed for VGF peptides. In fact, G cells showed immunoreactivity to virtually all region-specific antibodies to chromogranin A (Portela-Gomes & Stridsberg 2002), as opposed to the limited reactivity of VGF peptides we could demonstrate in such cell type.…”
Section: Discussionmentioning
confidence: 91%
“…A parallel is often drawn between VGF and the chromograninsecretogranin family of proteins, because of their selective localisation in secretory granules, as well as their role as precursors of multiple bioactive peptides (Helle 2004). Chromogranins, too, are differentially processed in gastric endocrine cells (Watkinson et al 1991, Watkinson & Dockray 1992, Portela-Gomes & Stridsberg 2002), although to a profile different from the one we observed for VGF peptides. In fact, G cells showed immunoreactivity to virtually all region-specific antibodies to chromogranin A (Portela-Gomes & Stridsberg 2002), as opposed to the limited reactivity of VGF peptides we could demonstrate in such cell type.…”
Section: Discussionmentioning
confidence: 91%
“…The bovine CGA gene contains an apparent polymorphism in the pancreastatin coding region, resulting in peptide variants containing either an arginine or a histidine residue. Reports of the presence of both peptides in a single bovine tissue suggest this is an allelic variation [27], since but a single mammalian CGA gene appears to exist [25,26,28], localized in the human genome to chromosome 14 [29,30].…”
Section: Structure Of the Cga Gene And Regulation Of Cga Gene Transcrmentioning
confidence: 99%
“…The extent of chromogranin A processing is highly tissuedependent: processing appears to be least complete in the adrenal medulla and progressively greater in intestine, stomach, peripheral nerves, and pancreas [27,103,[110][111][112]. The endocrine pancreas appears to exhibit the highest level of processing based on the ratio of intact CGA to fully processed /3-granin as well as pancreastatin [21,27,88]. CGA intragranular proteolytic processing in the endocrine pancreas is apparently completely calcium-dependent, and CGA is a much better substrate for PC2 than for PC1/3 kex2-1ike prohormone converting enzymes [88].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, several studies demonstrated that CgA could be degraded in a tissue-specific manner, which led to important disparities in the tissular distribution of the peptides released (Cetin and Grube, 1991;Curry et al, 1991;Watkinson et al, 1991). It is likely that the proteolysis properties may be responsible for the variability of the fragments found in normal and pathological tissues, blood or urine.…”
mentioning
confidence: 99%